Development and validation of a sensitive LC/MS/MS method for the determination of γ‐tocotrienol in rat plasma: application to pharmacokinetic studies. (20th April 2012) - Liang, Su; Bian, Xiaomei; Ma, Jing; Arogunjo, Motolani; Deorukhkar, Amit A.; Krishnan, Sunil; Xie, Huan
ABSTRACT γ‐Tocotrienol has attracted much attention owing to its multiple health benefits. This study developed and validated a simple, specific, sensitive and reliable LC/MS/MS method to analyze γ‐tocotrienol in rat plasma. Plasma samples (50 μL) were extracted with internal standard solution (25 ng/mL of itraconazole) in acetonitrile (200 μL) with an average recovery of 44.7% and an average matrix effect of −2.9%. The separation of γ‐tocotrienol and internal standard from the plasma components was achieved with a Waters XTerra® MS C18 column with acetonitrile–water as mobile phase. Analysis was performed under positive ionization electrospray mass spectrometer via the multiple reaction monitoring. The standard curve was linear over a concentration range of 10–1000 ng/mL with correlation coefficient values >0.997. The method was validated with intra‐ and inter‐day accuracy (relative error) ranging from 1.79 to 9.17% and from 2.16 to 9.66%, respectively, and precision (coefficient of variation) ranged from 1.94 to 9.25% and from 2.37 to 10.08%, respectively. Short‐term stability, freeze–thaw stability and the processed sample stability tests were performed. This method was further applied to analyze γ‐tocotrienol plasma concentrations in rats at various time points after administration of a 2 mg/kg single intravenous dose, and a pharmacokinetic profile was successfully obtained. Copyright © 2012 John Wiley & Sons, Ltd.